Contribution to the knowledge of nymphalidae fauna ( Lepidoptera: Rhopalocera ) in Kosovo - F. Zhushi; P. Bytyci; M. Ismail; M. Musliu (Trakia Journal of Sciences)
Insects of the order Lepidoptera are among the most explored in Europe. This order is presented with a rich variety, especially in the Balkan Peninsula, which includes also the state of Kosovo. In this paper the results of the research of Nymphalidae family in the region of Llapusha in Kosovo, specifically in the southern part of the mountain ranges of Shkoza, for the period April to July 2016 are presented. As a result of this research 35 species of Nymphalidae butterflies have been recorded, among them Melanargia russiae (Esper 1783) as a new species for Kosovo.This research is conducted five years after a first study of butterflies in this region took place and four years after the wildfire occurred in the area, which destroyed a large part of the vegetation. After this period, as a result of secondary succession, there is a renewal of vegetation, and a significant number of Nymphalidae butterflies.